Do New Drugs Increase Life Expectancy? A Critique of a Manhattan Institute Paper - Baker, Dean (Springer-Verlag, 2009)
A recent study published by the Manhattan Institute “Why Has Longevity Increased More in Some States than in Others? The Role of Medical Innovation and Other Factors,” purported to show that the more rapid adoption of new drugs has substantial benefits in the form of increased life expectancy, higher productivity and lower non-drug health care expenditures. This study has been cited as evidence supporting the more rapid acceptance of new drugs in Medicaid, Medicare, and other public programs and has helped to shape public debate on the value of new drugs. This analysis questions the key conclusions of the study. It points out that the key statistical regressions appear to be misspecified, since they show anomalies such as a negative correlation between income growth and life expectancy and find no relationship between education and productivity growth. Methodological flaws addressed include lack of adjustment for infant mortality rates; inadequate proxy measures of health status; lack of adjustment for ages of individuals and other sociodemographic factors; inherent problems with the definition of drug age, or ‘vintage;’ and the failure to consider reverse causation as an obvious explanation for several findings. The Manhattan Institute study does not provide reliable evidence for favoring adoption of newer drugs in either public or private health care programs.